Consider the recurrence relation
t_{(2^k)} = 2^{k} * (t_{(2^{k-1}}) + 5
t_{(1)} = 1



So far I have done this using repeated substitution (iteration).
I have no idea if what I am doing is correct, or if this is the proper way to go about it. Any help would be great.

Step 1:
t_{(2^k)} = 2^{k} * (t_{(2^{k-1}}) + 5

Step 2:
t_{(2^k)} = 2^{k-0} * (2^{k-1}  * (t_{(2^{k-2})})) + 5 + 5

t_{(2^k)} = 2^{2k-1} * (t_{(2^{k-2})}) + 5^2

Step 3:
t_{(2^k)} = 2^{2k-1} * (2^{k-2}  * (t_{(2^{k-3})})) + 5 + 5 + 5

t_{(2^k)} = 2^{3k-3} * (t_{(2^{k-3})}) + 5^3

Step 4:
t_{(2^k)} = 2^{3k-3} * (2^{k-3}  * (t_{(2^{k-4})})) + 5 + 5 + 5 + 5

t_{(2^k)} = 2^{4k-6} * (t_{(2^{k-4})}) + 5^4